Aktualisasi Keteladanan Guru PAI di Era Digital dan Kolaborasi Orang Tua dalam Pembentukan Karakter Religius Siswa di SMPN 3 Colomadu - Umar Muhtar Al Ghozali; Istanto Istanto (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to describe the actualization of Islamic Religious Education (PAI) teachers' exemplary behavior and collaboration with parents in shaping the religious character of students in the digital era at SMPN 3 Colomadu. The development of digital technology presents new challenges in the character formation process, particularly related to exposure to negative content, social media distractions, and low supervision of device use in the family environment. This study uses a phenomenological approach to deeply understand the experiences and perspectives of Islamic Religious Education (PAI) teachers in carrying out their roles. Data were collected through in-depth interviews, observation, and documentation, then analyzed through data reduction, data presentation, and conclusion drawing using triangulation techniques to maintain data validity. The results show that Islamic Religious Education (PAI) teachers have a strategic role as comprehensive educators who not only transfer knowledge but also instill moral values ​​through concrete role models in everyday life. Exemplary behavior (uswah hasanah) has proven to be an effective method in shaping students' religious character because it provides concrete examples to emulate. Furthermore, challenges of the digital era, such as social media distractions and exposure to negative content, require strengthened supervision and ongoing character development. Therefore, collaboration between teachers, schools, and parents is a key factor in creating consistent character development, so that religious values ​​can be more optimally internalized in students' lives.